Comparative Study In Patients Of Vaginal And Cervical Discharge: Syndromic Vs. Evidance Based Management (Indian Journal of Applied-Basic Medical Sciences, 2022)
Abstract: IntroductionThe syndromic management has been the cornerstone of management of  sexually transmitted infections (STIs) over the last few decades especially in developing  countries. But due to its inability to treat asymptomatic cases leading to undesirable sequeale,  it has received a lot of criticism recently. On the other hand, Evidence based management of  patients of vaginal and cervical discharge has lead to effective and timely management of  these patient but has increased the financial burden.Objective:The goal of the study is to compare syndromic vs. Evidence based approach in the  management of vaginal and cervical discharge. Method:The present study was conducted in the outpatient department of dermatology,  venereology & leprology of a tertiary care teaching hospital. 354 patients of clinical  impression of vaginal and cervical discharge were included in the study. Detailed history and  examination was recorded. Patients selected for syndromic management were managed as per  NACO guidelines. For evidence based management special investigations were carried out  and patients were managed accordingly. Result:Out of total 342 cases of VD, treated with syndromic and evidence based approach, p  value is significant for 7,14 and 21 days follow-up which means evidence based approach is  better than syndromic approach. Similar findings were observed in patients of cervical  discharge.Also, among CVV patients managed on lines of syndromic approach only 10%  showed improvement by end of one week. Conclusion:The control of STIs in resource-poor settings remains a major  challenge.Focus is now shifting towards a diagnostic model of STI care, given the  improving economic status of developing countries and availability of affordable point-of care testing. Also, various changes in the syndromic approach are needed immediately  for it to still remain relevant.
Keywords: vaginal; cervical; National AIDS Control Organization (NACO)